Oral contraceptive use as a determinant of plasma concentrations of perfluoroalkyl substances among women in the Norwegian Mother and Child Cohort (MoBa) study. (March 2018) - Rush, Elise L.; Singer, Alison B.; Longnecker, Matthew P.; Haug, Line S.; Sabaredzovic, Azemira; Symanski, Elaine; Whitworth, Kristina W.
Abstract: Objective: Because oral contraceptives (OC) tends to lessen menstrual fluid loss – a route of excretion for perfluoroalkyl substances (PFASs) – we hypothesized that such use would be positively associated with PFAS concentrations. Methods: This analysis was based on the Norwegian Mother and Child Cohort (MoBa) study. We included 1090 women from two previous substudies of women enrolled from 2003 to 2007. Characteristics of OC use were obtained at baseline: use in the past 12 months, duration and recency of use, age at first use. We examined log-transformed plasma concentrations of seven PFASs (perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnDA), perfluorohexane sulfonate (PFHxS), perfluoroheptane sulfonate (PFHpS), and perfluorooctane sulfonate (PFOS)). Linear regression analyses, adjusted for maternal age, menstrual cycle length, parity, and education, were used to examine whether OC use characteristics were determinants of PFAS concentrations. Results: Except for PFDA and PFUnDA, women who used OCs in the 12 months preceding the baseline interview had 12.9–35.7% higher PFAS concentrations than never OC users. To a lesser extent, past OC use was positively associated with PFASs (estimates ranged from 7.2–32.1%). Compared with never users, using OCs for 10 or more years was associated with increased PFAS concentrations, except for PFDA and PFUnDA (estimates for other PFASs ranged from 18.9–46.2%). We observed little effect of age at first OC use. Conclusions: This analysis shows that characteristics of OC use, and duration of use in particular, may be important considerations when investigating relationships between women's reproductive outcomes and PFASs. Highlights: Women who use oral contraceptives have higher plasma concentrations of perfluoroalkyl substances. Lifetime duration of oral contraceptive use may be more important than recency of use. Little effect of age at first use was observed.